Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I need to calculate value of $1000^{th}$ derivate of the following function at $0$:

$$ f(x) = \frac{x+1}{(x-1)(x-2)} $$

I've done similar problems before (e.g. $f(x)= \dfrac{x}{e^{x}}$) but the approach I've used would not work in this case and I believe I should expand this function into a power series. Could you please give me any hints on how to do it?

share|cite|improve this question
Partial fractions? – David Mitra Jan 26 '13 at 19:29
"I believe I should expand this function into a power series" wouldn't work because you need the derivatives to get the Taylor expansion coefficients anyway. – Fixed Point Jan 26 '13 at 19:47
up vote 6 down vote accepted

Hint: Note that $f(x)=\frac{3}{x-2}-\frac{2}{x-1}$ and if $g(x)=\frac{1}{x-a}$ then $g^n(x)=\frac{(-1)^n n! }{(x-a)^{n+1}}$ where $a$ is a constant and $g^n(x)$ is the $n$-th derivative of $g(x)$.

Here $$\begin{align} \frac{A}{x-2}+\frac{B}{x-1} &=\frac{x+1}{(x-2)(x-1)}\\ \implies A(x-1)+B(x-2) &= x+1 \\ \implies x(A+B)+(-A-2B) &= x+1\end{align}$$ From this we get $$\begin{align}A+B &=1 \\ -A-2B &=1 \end{align}$$

share|cite|improve this answer
Your formula for the $n$-th derivative of $g$ is not correct. You miss some factorial. – 1015 Jan 26 '13 at 19:35
@julien : you are right . I miss the factorial part. I will edit it. – Argha Jan 26 '13 at 19:36

Starting with the partial fraction decomposition $$f(x)=\frac{3}{x-2}-\frac{2}{x-1}\;,$$ use the geometric series sum to write

$$\begin{align*} f(x)&=-\frac32\cdot\frac1{1-\frac{x}2}+2\frac1{1-x}\\\\ &=2\sum_{n\ge 0}x^n-\frac32\sum_{n\ge 0}\left(\frac{x}2\right)^n\\\\ &=\sum_{n\ge 0}\left(2-\frac32\left(\frac12\right)^n\right)x^n\\\\ &=\sum_{n\ge 0}\left(2-\frac3{2^{n+1}}\right)x^n\;. \end{align*}$$

Then equate this with the Maclaurin series

$$f(x)=\sum_{n\ge 0}\frac{f^{(n)}(0)}{n!}x^n$$

to get $$\frac{f^{(n)}(0)}{n!}=2-\frac3{2^{n+1}}$$ and then


share|cite|improve this answer

As suggested by Argha and David Mitra, begin with the decomposition into partial fractions: $$ f(x)=\frac{3}{x-2}-\frac{2}{x-1}. $$ Now if $g(x)=\frac{1}{x-a}$ for some constant $a$, then a proof by induction quickly shows that $$ g^{(n)}(x)=\frac{(-1)^nn!}{(x-a)^{n+1}}. $$ It follows that $$ f^{(1000)}(x)=\frac{3\cdot 1000!}{(x-2)^{1001}}-\frac{2\cdot 1000!}{(x-1)^{1001}}. $$ Now make $x=0$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.